Collagen Assembly at the Cell Surface: Dogmas Revisited - Moses Musiime; Joan Chang; Uwe Hansen; Karl E. Kadler; Cédric Zeltz; Donald Gullberg (Cells, 2021)
With the increased awareness about the importance of the composition, organization, and stiffness of the extracellular matrix (ECM) for tissue homeostasis, there is a renewed need to understand the details of how cells recognize, assemble and remodel the ECM during dynamic tissue reorganization events. Fibronectin (FN) and fibrillar collagens are major proteins in the ECM of interstitial matrices. Whereas FN is abundant in cell culture studies, it is often only transiently expressed in the acute phase of wound healing and tissue regeneration, by contrast fibrillar collagens form a persistent robust scaffold in healing and regenerating tissues. Historically fibrillar collagens in interstitial matrices were seen merely as structural building blocks. Cell anchorage to the collagen matrix was thought to be indirect and occurring via proteins like FN and cell surface-mediated collagen fibrillogenesis was believed to require a FN matrix. The isolation of four collagen-binding integrins have challenged this dogma, and we now know that cells anchor directly to monomeric forms of fibrillar collagens via the α1β1, α2β1, α10β1 and α11β1 integrins. The binding of these integrins to the mature fibrous collagen matrices is more controversial and depends on availability of integrin-binding sites. With increased awareness about the importance of characterizing the total integrin repertoire on cells, including the integrin collagen receptors, the idea of an absolute dependence on FN for cell-mediated collagen fibrillogenesis needs to be re-evaluated. We will summarize data suggesting that collagen-binding integrins in vitro and in vivo are perfectly well suited for nucleating and supporting collagen fibrillogenesis, independent of FN.